Energy cost of seed drying - Weerachet Jittanit; George Srzednick; Robert Driscoll (ASEAN Journal on Science and Technology for Development, 2017)
In this work, the energy costs of drying corn, rice and wheat seeds between 3 drying options were compared. They consisted of 1) two-stage drying by using fluidised beddrye (FBD) in the 1ststage and in-store dryer (ISD) in the 2ndstage, 2) single-stage drying by fixed bed dryer (FXD) and 3) two-stage drying by using FXD in the 1ststage and ISD in the 2ndstage. The drying conditions selected for comparison were proved to be safe for seed viability by the previous studies. The results showed that the drying options 2 and 3 consumed less energy than option 1. However, the benefits from lower energy cost must be weighed against some advantages of using FBD. Furthermore,it appeared that running the burners of FXD and ISD for warming up the ambient air during humid weather condition could shorten drying time significantly with a little higher energy cost.